Please find the sum of these problems with the steps:
1. (3x^5-2x^4+6x) and (2x^5+9x^4+4x)
2. (7x^2+9x^4+4-6x^3)-(8-4x^3+4x^4+5x^2)
Sum just means to add.
(3x^5-2x^4+6x) + (2x^5+9x^4+4x) ............expand the brackets
= 3x^5-2x^4+6x + 2x^5+9x^4+4x ..............now group like terms
= 3x^5 + 2x^5 - 2x^4 + 9x^4 + 6x + 4x ......now add the like terms
= 5x^5 + 7x^4 + 10x
(7x^2+9x^4+4-6x^3)-(8-4x^3+4x^4+5x^2) .............expand the brackets, the minus sign in front of the second set of brackets changes the sign of everything in that set of brackets.2. (7x^2+9x^4+4-6x^3)-(8-4x^3+4x^4+5x^2)
= 7x^2 + 9x^4 +4 -6x^3 - 8 + 4x^3 - 4x^4 - 5x^2 ...now group like terms
= 9x^4 - 4x^4 - 6x^3 + 4x^3 + 7x^2 - 5x^2 + 4 - 8 ..now add like terms
= 5x^4 - 2x^3 + 2x^2 - 4